Neutron diffraction study of crystal structure of K(NH)Cl (x=0.2, 0.8) mixed salts - G, Batdemberel; D, Sangaa; Sh, Chadraabal; H, Fuess; A, Skomorokhov; L.S, Smirnov; A.I, Beskrovny (Scientific transaction of the National University of Mongolia. Physics, 2022)
TOF neutron diffraction study shows that at the room temperature K0.2(NH4)0.8CI and K0.8(NH4)0.2CI compounds form cubic crystal lattices with the corresponding space groups: Fm3m and I'm3m. It was established considerable distortion of hydrogen atoms in these structures from their initial positions Kg.